Powercoaching Program and Oral Discourse Competence of Grade 10 Students - Sucion, Richard B.; Subillaga, Rebecca D.; Ambayon, Cristobal M. (International Journal of Educational Technology and Learning, 2021)
Powercoaching is an intervention program which aims to enhance the oral discourse competence of the students. It highlights various activities that can help students with speaking difficulties. It was conducted among Grade 10 students of New Pangasinan National High School during the School Year 2019-2020. This study dealt to determine the level of effectiveness of the powercoaching program in terms of its content, relevance, instructional quality, and acceptability. Experimental research design was employed to determine the level of oral discourse competence of the students in terms of grammar, pronunciation, spontaneity, substance, organization, and diction. The findings of the study showed that the program was excellent and passed the quality standard set by the validators. The level of oral discourse competence of the students in their onset test were both in approaching proficient. The students were either struggling or have not acquired the knowledge, skills and understanding in public speaking. The difference between the levels of oral discourse competence of the students reveals that among the two groups of students, one group performed better in the outset test. The experimental group significantly increased their performance with proficient level compared to the control group. Moreover, there was a significant difference between the mean gain scores of the control and experimental groups. Students under experimental group have gained higher mean than the control group. Hence, the powercoaching program greatly influenced the students’ oral communicative competence. The developed program is then recommended for teachers’ utilization as part of their intervention strategies.